2004
DOI: 10.2337/diacare.27.10.2464
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Diabetes in Middle-Aged Men Is Related to Sleep Disturbances

Abstract: OBJECTIVE -Sleep deprivation in healthy men has been experimentally found to result in disturbances in glucose metabolism and in sympathovagal imbalance. The aim of the present study was to investigate whether sleep disturbances and elevated resting heart rate are associated with increased risk of developing diabetes. RESEARCH DESIGN AND METHODS-A group of 6,599 initially healthy, nondiabetic men aged 44.5 Ϯ 4.0 years took part in a prospective, population-based study in Malmö , Sweden. The incidence of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
153
3
19

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(180 citation statements)
references
References 42 publications
(50 reference statements)
5
153
3
19
Order By: Relevance
“…The current data further indicate that not only reduced sleep duration but also reduced sleep quality may play a role in diabetes risk. Our laboratory findings are consistent with a body of epidemiologic evidence linking short or poor sleep and increased incidence of type 2 diabetes (17)(18)(19)(20)(36)(37)(38). Taken together, the current evidence suggests that strategies to improve sleep duration and quality should be considered as a potential intervention to prevent or delay the development of type 2 diabetes in at-risk populations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The current data further indicate that not only reduced sleep duration but also reduced sleep quality may play a role in diabetes risk. Our laboratory findings are consistent with a body of epidemiologic evidence linking short or poor sleep and increased incidence of type 2 diabetes (17)(18)(19)(20)(36)(37)(38). Taken together, the current evidence suggests that strategies to improve sleep duration and quality should be considered as a potential intervention to prevent or delay the development of type 2 diabetes in at-risk populations.…”
Section: Discussionsupporting
confidence: 74%
“…It is possible that, under more chronic conditions, insulin secretion might increase to a level sufficient to compensate for the decrease in S.I. However, evidence to the contrary has been obtained in four independent prospective epidemiologic studies showing that poor sleep quality is associated with an increase in the risk of incident type 2 diabetes (17)(18)(19)(20). We observed an elevation in sympathovagal balance, which could be involved both in the decrease in S.I.…”
Section: Discussionmentioning
confidence: 41%
“…For example, Cushing's syndrome, sleeping disorders, work stress and schizophrenia [30][31][32][33] appeared to be associated with an increased level of cortisol and also with an increased risk of type 2 diabetes and insulin resistance, although studies on sleep disorders showed inconsistent results regarding risk of diabetes [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] A growing body of epidemiological evidence supports an association between short sleep duration and the risk of obesity [57][58][59][60][61] and type 2 diabetes. [62][63][64][65][66] The potential mechanisms by which sleep deprivation may predispose to obesity are: (1) an alteration of the neuroendocrine control of appetite characterized by a decrease in the levels of the anorexigenic hormone leptin and an increase in the levels of the orexigenic hormone ghrelin; (2) an increased opportunity to eat; (3) an altered thermoregulation; and (4) an increased fatigue leading to reductions in physical activity. 67 Furthermore, physiological data suggest that short-term partial sleep restriction leads to striking alterations in metabolic function including decreased carbohydrate tolerance and insulin resistance.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%